Android-based System Monitoring of Supporting Variables for Nursery-Plant Growth in Plantation Areas - Adis Kusyadi Nugraha; Giva Andriana Mutiara; Tedi Gunawan; Gita Indah Hapsari (JOIV : International Journal on Informatics Visualization, 2023)
In cultivating timber trees, farmers must pay attention to the seed selection with superior heredity, hormones, and the condition of the plantation area that supports the growth of nursery plants properly. Several factors that support the growth of nursery plants are nutritional factors, sunlight, temperature, soil pH, water, and soil moisture. In terms of effectiveness and ease of access to information in monitoring the supporting condition factors and facilitating the farmers, an Android-based monitoring system was built to monitor the growth of nursery plants. The system consists of several sensors, such as a soil pH sensor, UV light sensor, and soil moisture sensor embedded with Raspberry pi and firebase. The proposed system was examined on a plantation area of 900 square meters. The testing is conducted by placing a combination of 4 to 8 sensors in the plantation area. Data from each sensor is processed by calculating the average, and the results are rounded to the nearest value. The test stated that to monitor an area of 900 square meters, the area with five sensors implanted can be used as the optimal implementation. Apart from economic reasons, the minor rounding error equals 8.25% compared to the number of other sensors. The results that are informed to the farmers are also within the appropriate range. There are no significant differences, and this approach can be used to implement in a broader area